2022
DOI: 10.1186/s12920-022-01294-w
|View full text |Cite
|
Sign up to set email alerts
|

Somatic targeted mutation profiling of colorectal cancer precursor lesions

Abstract: Background Most colorectal cancers (CRC) arise from precursor lesions. This study aimed to characterize the mutation profile of colorectal cancer precursor lesions in a Brazilian population. Methods In total, 90 formalin-fixed paraffin-embedded colorectal precursor lesions, including 67 adenomas, 7 sessile serrated lesions, and 16 hyperplastic polyps, were analyzed by next-generation sequencing using a panel of 50 oncogenes and tumor suppressor gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…While studying nondysplastic crypts underneath the neoplastic canopy of nonpolypoid and polypoid sporadic colon adenomas (30), we noticed that some of the crypts in the pedicle exhibited haphazardly distributed Ki67-labeled cells and p53upregulated cells, reaching the luminal aspect of nondysplastic crypts (30). It was suggested that the relocation of the normal Ki67 domains in the cells of the crypts of the stalk and the occurrence of p53-up-regulated cells in the same crypts evolved as a result of somatic mutations (29). This suggestion was validated in a recent mega-analysis of colorectal transcriptomes of histologically normal mucosa adjacent to colorectal carcinomas (CRC) (31).…”
Section: Discussionmentioning
confidence: 99%
“…While studying nondysplastic crypts underneath the neoplastic canopy of nonpolypoid and polypoid sporadic colon adenomas (30), we noticed that some of the crypts in the pedicle exhibited haphazardly distributed Ki67-labeled cells and p53upregulated cells, reaching the luminal aspect of nondysplastic crypts (30). It was suggested that the relocation of the normal Ki67 domains in the cells of the crypts of the stalk and the occurrence of p53-up-regulated cells in the same crypts evolved as a result of somatic mutations (29). This suggestion was validated in a recent mega-analysis of colorectal transcriptomes of histologically normal mucosa adjacent to colorectal carcinomas (CRC) (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although GEMMs and carcinogenic‐induced models are important tools in basic research and drug discovery of CRC, they still fail to remodel some critical features of clinical trials 38 . These models lack genetic consistency, a diversified diet, varied lifestyle, and an equal microbiome similar to human CRCs, all of which affect the disease's onset and course 39,40 . Moreover, the absence of inter‐tumoral heterogeneity because of poor genetic heterogeneity in inbred mice compared to outbred humans also decreases the potential of results in translational clinical research.…”
Section: Typical Crc Preclinical Modelsmentioning
confidence: 99%
“… 38 These models lack genetic consistency, a diversified diet, varied lifestyle, and an equal microbiome similar to human CRCs, all of which affect the disease's onset and course. 39 , 40 Moreover, the absence of inter‐tumoral heterogeneity because of poor genetic heterogeneity in inbred mice compared to outbred humans also decreases the potential of results in translational clinical research. These differences urge us to develop new models that more exactly display the characteristics of human CRCs.…”
Section: Typical Crc Preclinical Modelsmentioning
confidence: 99%